IMPLEMENTATION OF BANDLIMITED IMPEDANCE INVERSION IN DEPTH DOMAIN SEISMIC DATA, âXYZâ FIELD NORTHERN EAST JAVA BASIN - Yuniar Latifah, Fara
The development of seismic migration procedures in the depth domain has been carried out in the last few decades. Seismic data in the depth domain has the advantage that it can produce subsurface images that are better when compared to time-domain seismic data. However, in processing the data, the depth domain seismic data has a limitation that is the convolution process cannot be directly carried out in the depth domain because the wavelet depth domain has non-stationary characteristics. One way to overcome this is by transforming the depth domain seismic into the pseudo-depth domain. The convolution process is then carried out in the pseudo-depth domain and the trace seismic pseudo-depth domain will be transformed back into the "true" depth domain. This research is intended to implement depth domain seismic data processing techniques using the pseudo-depth transformation method to obtain results in the form of trace seismic domains "true" depth. The seismic inversion process is also carried out using the bandlimited impedance (BLIMP) method. The BLIMP seismic inversion method can accommodate the limitation of seismic frequency bandwidth in the form of low-frequency implied from log data trends. Therefore, the low-frequency cut-off value used in BLIMP inversion plays an important role in the impedance of the inversion results. In this study, it was found that the pseudo-depth transformation process can overcome the limitations of the depth domain data and does not change the frequency content of the depth domain data and the traces of the "true" depth seismic domain are obtained which on each wavelet was widened when passing through different media with greater speed and the low-frequency cut-off value of the inversion BLIMP which produces the optimum impedance is 25 Hz in synthetic data and 10 Hz in real data.